B-doped nano-hydroxyapatite facilitates proliferation and differentiation of osteoblasts - Qiao Kang; Wenhao Wang; Shengtao Wu; Ganggang Hu (Journal of Orthopaedic Surgery and Research, 2025)
Abstract Purpose We aimed to explore the mechanism by which Boron-doped nano-hydroxyapatite (B-nHAp) facilitates the proliferation and differentiation of osteoblasts through controlled release of B. Methods B-nHAp characterization was accomplished by means of X-ray diffraction, scanning electron microscopy, inductively coupled plasma mass spectrometry, and transmission electron microscopy. Human bone marrow mesenchymal stem cells (hBMSCs) were subjected to flow cytometry, alizarin red S staining, and cell counting kit-8 assay for proliferation and differentiation determination. Western blotting for protein expression detection together with real-time quantitative polymerase chain reaction for mRNA expression measurement were carried out on those related to hBMSC proliferation and differentiation. Immunofluorescence staining was conducted to determine the activity of the Wnt/β-catenin signaling pathway. Results B-nHAp particles had structured configuration and uniform size, and a typical nHAp crystal structure. The B content in B-nHAp was in line with expectation. hBMSCs displayed stemness. B-nHAp significantly facilitated the proliferation of hBMSCs, and significantly more mineralized nodules formed in the B-nHAp group. B-nHAp significantly upregulated the expressions of marker molecules related to hBMSC proliferation and differentiation. B-nHAp boosted the activity of the Wnt/β-catenin signaling pathway. Conclusion B-nHAp modulates the Wnt/β-catenin signaling pathway to significantly enhance the proliferative and differential abilities of osteoblasts, potentially as an efficient material for bone repair.